Debt Transparency in Developing Economies - Rivetti, Diego (World Bank, Washington, DC, 2021)
Analyzing public debt in low-income developing countries (LIDCs) is like solving a puzzle with many missing pieces. Forty percent of LIDCs have not published any sovereign debt data in the last two years. Public debt data disclosed in different publications show discrepancies of up to 30 percent of GDP across sources, and relative to the records of relevant authorities. Over 15 LIDCs have outstanding collateralized debt but no details of the collateralization are provided in official statistics. Restructuring of bilateral and commercial debt is often handled privately. All these problems have different origins and implications. Yet, they all amount to a lack of transparency. The international community has become acutely aware of the importance of debt transparency after recent cases of "hidden debt" The "Tuna Bond" case in Mozambique highlighted the dangers of inadequate debt transparency. In 2016 two large previously unreported loans totaling 1.15 billion US Dollars —equal to about 9 percent of the country’s GDP—were revealed. As a result, donor support was frozen, the economy plunged, and the government was forced to make deep cuts in public spending. The biggest losers were poor Mozambiquans. Nontransparent public debt can quickly alter the lives of millions of ordinary citizens. This report is the first comprehensive assessment of debt transparency in LIDCs. It presents a complete picture of the current challenges and the pending policy agenda for all stakeholders. It draws upon new databases and surveys to take stock of key gaps in debt reporting, borrowing practices and legal frameworks, offering a detailed and timely view on the current state of debt transparency in LIDCs. It also synthesizes recent studies and policy discussions on debt transparency and offers practical policy recommendations required to further improve debt transparency in LIDCs.